2021
DOI: 10.1177/10497323211044468
|View full text |Cite
|
Sign up to set email alerts
|

Surprise Reveals the Affective-Moral Economies in Cancer Illness Narratives

Abstract: Emotions, like joy and sorrow, feature in illness narratives, dramatizing stories of becoming: sick, well, controlled, in control. However, brief emotions, such as surprise, have received limited analytic attention in cancer illness narratives. Drawing on 20 interviews with 11 participants with diverse cancer diagnoses, along with the 455 photographs they produced for this study, we address the complex interactions between discourse, societal expectations, and perceptions in moral-affective economies. Tracing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
(89 reference statements)
1
4
0
Order By: Relevance
“…Participants explained that they brought the results of their searches and discussions to their healthcare providers for further consideration and conversation. The findings of Abdulla et al [59] on information seeking behaviors on patients and their care were similar to the findings of this study, in that patients and their caregivers sought information from multiple sources, with many relying on Internet sources for information (as was also found by [60]), and that they wanted to share and discuss the information they found with their healthcare providers. Conducting their own independent research seemed to offer participants in the current study a sense of control and authority during the diagnosis process.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Participants explained that they brought the results of their searches and discussions to their healthcare providers for further consideration and conversation. The findings of Abdulla et al [59] on information seeking behaviors on patients and their care were similar to the findings of this study, in that patients and their caregivers sought information from multiple sources, with many relying on Internet sources for information (as was also found by [60]), and that they wanted to share and discuss the information they found with their healthcare providers. Conducting their own independent research seemed to offer participants in the current study a sense of control and authority during the diagnosis process.…”
Section: Discussionsupporting
confidence: 89%
“…It is understandable that a long period of diagnostic uncertainty along with worsening symptoms would motivate persons to seek information from the Internet. The well-known concerns about the limited reliability of online health information [59][60][61], which was acknowledged by some participants in this study, heighten the importance of timely information from healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…Missel et al [12] found that patients with operable lung cancer distanced themselves from acknowledging that they had cancer, despite simultaneously expressing a sense of shock. Plage and Olson [32] demonstrated how surprise and shock is a sociocultural issue appearing in the face of an unanticipated cancer diagnoses. However, staying cool might be a certain narrative type of emotional reaction to cancers that are situated as individual risk and deservedness and where cultural frames of deservedness and responsibility are narrative resources influencing possible emotional reactions to a lung cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…26 In the same sense, the results would have implications for clinical practice and health professionals, especially in communication with patients, and in the morals implications of discourses that relate positive thoughts with etiology and treatment of the cancer. 27 Attributing the disease and treatment to thoughts and emotions, the responsibility for the etiology of cancer and therapeutic success is transferred to the patient. Positive thinking becomes a moral requirement that generates a double burden for patients: the burden of the biological disease, and the internal and external burden to think positively, since if the disease progresses, the patient feels guilty and ashamed for his inability to overcome the disease.…”
Section: Introductionmentioning
confidence: 99%